2000
DOI: 10.1128/jvi.74.15.6946-6952.2000
|View full text |Cite
|
Sign up to set email alerts
|

CCR8 on Human Thymocytes Functions as a Human Immunodeficiency Virus Type 1 Coreceptor

Abstract: To determine whether human immunodeficiency virus type 1 (HIV-1) coreceptors besides CXCR4 and CCR5 are involved in HIV-1 infection of the thymus, we focused on CCR8, a receptor for the chemokine I-309, because of its high expression in the thymus. Similar levels of CCR8 mRNA were detected in immature and mature primary human thymocytes. Consistent with this, [125 I]I-309 was shown to bind specifically and with similar affinity to the surface of immature and mature human thymocytes. Fusion of human thymocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 47 publications
0
36
1
Order By: Relevance
“…CCR8 is a beta chemokine receptor with a known role in induction of chemotaxis in Th2 cells via its two ligands CCL1 and CCL18 [50], and functions as a co-receptor for enveloped viruses including HIV [51,52]. The CCR8 axis has been found to be activated in urothelial and renal carcinomas resulting in immune response impairment, and it is responsible for apoptosis inhibition in lymphoma [53,54].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CCR8 is a beta chemokine receptor with a known role in induction of chemotaxis in Th2 cells via its two ligands CCL1 and CCL18 [50], and functions as a co-receptor for enveloped viruses including HIV [51,52]. The CCR8 axis has been found to be activated in urothelial and renal carcinomas resulting in immune response impairment, and it is responsible for apoptosis inhibition in lymphoma [53,54].…”
Section: Resultsmentioning
confidence: 99%
“…CCL5 was also shown to strongly induce uptake of (cellular, non-viral) EVs from uninfected T lymphocytes [84]. Of note, it was reported that enveloped viruses, such as HIV, can use chemokine receptors as co-receptors, including CCR8 [51,8587]. Moreover, natural ligands can compete with these viruses for the co-receptors, inhibiting viral uptake [88,89].…”
Section: Discussionmentioning
confidence: 99%
“…However, loss of CD4 ϩ thymocytes is also observed after infection with R5 isolates, although at a later time postinfection (32,66). The chemokine receptors CCR3, CCR4, CCR8, CCR9, and CXCR6 are also expressed in the thymus and may be used as coreceptors for HIV, as recently reported for CCR8 (20,30,44,45,52,87).…”
mentioning
confidence: 81%
“…7). In addition, recent studies in our laboratory have shown that the presence of the CD27 ϩ population at the moment of infection is essential for virus replication in thymocytes in vitro (Gurney and Uittenbogaart, unpublished), further delineating the mature thymocyte subset in which we and others observe HIV expression (10, 28,44,56). More-recent studies with an X4 variant suggest that IL-7 favors the persistence of HIV in mature CD4 ϩ CD8 Ϫ CD3 ϩ thymocytes, which we characterized here as being CD27 ϩ (28).…”
Section: Vol 76 2002 Replication In the Thymus Of Hiv Isolates Frommentioning
confidence: 94%
“…HIV-1 infects cells by recognition of the CD4 receptor in combination with a coreceptor, which is either the chemokine receptor CCR5 or CXCR4 (reviewed in refs. 7,8). HIV-1 can use other coreceptors to some extent in vitro, but these receptors do not seem to play a major role in vivo.…”
Section: Introductionmentioning
confidence: 99%